Pemanfaatan Logam Aluminium (Al) Pada Kaleng Minuman Soda Menjadi Tawas - Loisa Rosalia Sitompul; Elvi Yenie; Shinta Elystia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The waste problem in Indonesia is a very complex issue. The example of waste that have huge amount of quantities is beverages cans. Waste cans can be reduced by utilizing from recycle the aluminum content to be the main material of potassium alum (KAI (SO4) 2.12H2O). In this study used carbonated drinks. The concentration of aluminium in soda cans is 84%, the concetration can be determined using Atomic Absorption Spectrophotometry (ASS). The variables used in this study is variation of KOH concentration whitin 20%, 30%, and 40% and the variation of H2SO4 concentration whitin 6M, 8M, and 10 M. From the results of this study showed optimum yield is 98.52% occurred at a concentration of 40% KOH and H2SO4 8M. Characteristic of this alum is having insoluble part in water of 0% and 5.39% aluminium in alum.Keywords : Cans, potassium alum